Oxygen in Must and Wine: A review - du Toit, W.J.; Marais, J.; Pretorius, I.S.; du Toit, M. (South African Journal of Enology and Viticulture, 2017)
Oxygen can play an important role during the winemaking process. It can influence the composition and quality of the must and wine. Phenolic compounds are the main substrates for oxidation in must and wine. Oxygen addition leads to colour changes and the polymerisation of phenolic molecules in wine. Oxygen can, however, also influence the flavour and microbial composition of wine drastically, with certain off-flavours being formed and spoilage micro-organisms able to grow at too high oxygen additions to wine. A state-of-the-art, up-to-date review on the effects of oxygen in must and wine has, however, not been published recently. This review focuses on the effects of oxygen in must, during alcoholic fermentation, extended lees contact and during ageing of white and red wines. The effects it has on acetic acid bacteria and Brettanomyces are also discussed, as well as micro-oxygenation, a relative new technique used in wine production.